2019
DOI: 10.1111/acer.14066
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Exposure Increases miR‐140 in Extracellular Vesicles: Implications for Fetal Neural Stem Cell Proliferation and Maturation

Abstract: Background: Neural stem cells (NSCs) generate most of the neurons of the adult brain in humans, during the mid-first through second-trimester period. This critical neurogenic window is particularly vulnerable to prenatal alcohol exposure, which can result in diminished brain growth. Previous studies showed that ethanol (EtOH) exposure does not kill NSCs, but, rather, results in their depletion by influencing cell cycle kinetics and promoting aberrant maturation, in part, by altering NSC expression of key neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 86 publications
3
42
1
Order By: Relevance
“…BMP2 was identified as the hub regulatory gene of miR-140-5p, which accounted for 6.96% of the total miRNA reads in P3-DP-EVs. Although few studies have investigated the role of miR-140-5p in dermatology, miR-140-5p expression is known to promote proliferation in dental pulp stem cells (Sun et al, 2017), neural stem cells (Tseng et al, 2019), and chondrocytes (Tao et al, 2017;Wang Z. et al, 2018). We showed that overexpression of miR-140-5p in human HFs was confirmed to stimulate ORSC and MxCs proliferation by treatment with overexpressed vesicular miR-140-5p, but was restricted by vesicular miR-140-5p inhibition.…”
Section: Discussionmentioning
confidence: 81%
“…BMP2 was identified as the hub regulatory gene of miR-140-5p, which accounted for 6.96% of the total miRNA reads in P3-DP-EVs. Although few studies have investigated the role of miR-140-5p in dermatology, miR-140-5p expression is known to promote proliferation in dental pulp stem cells (Sun et al, 2017), neural stem cells (Tseng et al, 2019), and chondrocytes (Tao et al, 2017;Wang Z. et al, 2018). We showed that overexpression of miR-140-5p in human HFs was confirmed to stimulate ORSC and MxCs proliferation by treatment with overexpressed vesicular miR-140-5p, but was restricted by vesicular miR-140-5p inhibition.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, an in vivo model of developing zebrafish demonstrated that miR-153 levels decreased after ethanol exposure, consequently revealing impaired neurobehavioral development [ 102 ]. In vitro cultured NSCs were also used to understand the role of EVs in NSC development and differentiation during ethanol exposure [ 48 ]. In these studies, miR-140-3p was identified as another important miRNA affected by ethanol treatment, indicating that ethanol influences the expression of key differentiation-associated mRNA transcripts.…”
Section: Evs In Developmental Pathology Of the Nervous Systemmentioning
confidence: 99%
“…Additionally, miR-155 deficiency or TLR4 knockout protected mice from alcohol-induced neuroinflammation [148]. A fetal neural-stem-cell (NSCs) study found that 47 miRNAs, including miR-140-3p, miR-15b-3p, miR-340-5p, and miR-674-5p, were significantly upregulated in EVs from alcohol-treated NSCs [149]. Overexpression of miR-140-3p increased the number of S-phase cells and decreased the number of G 0 /G 1 cells, suggesting an increase in cell proliferation.…”
Section: Alcoholmentioning
confidence: 99%
“…During NSC differentiation, overexpression of miR-140-3p increased the mRNA expression of GFAP (astrocytic marker) and decreased the expression of PDGFR α (an oligodendrocyte marker) as well as DCX and NeuN (neuronal markers), potentially promoting aberrant astrocytic differentiation of NSCs at the expense of differentiating to other cell lineages. This dysregulation of miRNA content may contribute to abnormal neurodevelopment linked with fetal alcohol syndrome disorder [ 149 ].…”
Section: Drugs Of Abusementioning
confidence: 99%